The fNIRS evaluation of frontal and temporal lobe cortical activation in Chinese first-episode medication-naïve and recurrent depression during a verbal fluency task - Yang, Ting; Wang, Hongyu; Dai, Haiyue; Hui, Juan; Zhang, Jintong; Li, Juan; Cui, Guimei; Wang, Juan; Mu, Junlin; Zhang, Zhaohui (Frontiers in Psychiatry, 2023)
Background Functional near-infrared spectroscopy (fNIRS) identifies neurophysiological differences between psychiatric disorders by assessing cortical hemodynamic function. Few trials have studied differences in brain functional activity between first-episode medication-naïve depression patients (FMD) and recurrent major depression (RMD). We aimed to determine the differences between FMD and RMD in oxygenated hemoglobin concentration ([oxy-Hb]), and to investigate the correlation between frontotemporal cortex activation and clinical symptoms. Methods We recruited 40 patients with FMD, 53 with RMD, and 38 healthy controls (HCs) from May 2021 to April 2022. Symptom severity was assessed with the 24-item Hamilton Depression Rating Scale (HAM-D) and the Hamilton Anxiety Rating Scale (HAM-A). A 52-channel fNIRS measured changes in [oxy-Hb] during VFT performance. Results Both patient groups performed poorly during the VFT task compared with HC (FDR p < 0.05), but there was no significant difference between the two patient groups. Analysis of variance showed that mean [oxy-Hb] activation was lower in both the frontal and temporal lobes in the MDD group compared with HCs (FDR p < 0.05). Additionally, patients with RMD had a significantly lower hemodynamic response in the right dorsolateral prefrontal cortex (DLPFC) and dorsal frontal pole cortex (DFPC) than patients with FMD (FDR p < 0.05). No significant correlation was found between changes in mean [oxy-Hb] and either medical history or clinical symptoms (FDR p < 0.05). Conclusion The presence of different neurofunctional activity in some of the same brain regions in FMD and RMD patients implied a link between the level of complexity activation in frontal regions and the stage of MDD. Cognitive impairment may already be present at the beginning of an MDD episode. Clinical trial registration www.chictr.org.cn, identifier ChiCTR2100043432.